Biocompatible glass composite system – some physical- mechanical properties of the glass composite matrix system - Staniewicz-Brudnik, Barbara; Lekka, Małgorzata; Jaworska, Lucyna; Wilk, Włodzimierz (Oficyna Wydawnicza Politechniki Wrocławskiej, 2010)
In this work there are discussed the physical-mechanical properties of the glass CaO–SiO2–P2O5–Na2O system (FB3) assigned for the glass composite matrix system using the following research methods: spectral chemical analysis (XRF), SBET specific surface area analysis, XRD investigation, observation with a scanning electron microscope (SEM), wettability of the submicrocrystalline sintered corundum (ssc) by the glass system, microhardness test and DTA measurement. It was found that theoretical oxide chemical composition was close to that obtained from the spectral chemical analysis (XRF), the prolongated high energetic milling of the glass system did not have any significant influence on the specific surface area of grains (from 0.9159 m2/g after 5-hour milling to 1.9241 m2/g after 20-hour milling process only), in comparison to the specific surface area of the ssc, wettability investigation of the submicrocrystalline sintered corundum by the glass FB3 system showed the value of contact angle (θ < 45°), and the microhardness value of about 6 GPa. On the basis of DTA results the sintering temperature of bioglass composite with the strengthening phase from the submicrocrystalline sintered corundum was determined and, using the previous experience, the way of producing composite was proposed. The calculation of the thermodynamic stability of the glass system-strengthening phase by VCS algorithm showed the presence of 4–5 solid compounds. The results of the fibroblast (cell line CCL 110, Promochem LG) preliminary culture investigation on the bioglass composite substrate were positive. The best results were obtained in the case of the biocomposite with the smallest amount of strengthening phase.
Optica Applicata, Vol. 40, 2010, nr 2, s. 403-412
Keywords: optyka; glass of CaO–SiO2–P2O5–Na2O system; submicrocrystalline sintered corundum; bioglass composite; XRF; XRD; DTA; contact angle; VCS algorithm; fibroblast culture